Evaluasi Pelaksanaan Alokasi Dana Desa (ADD) di Bidang Ekonomi - Imam, Sadrul; Daaris, Yuli Yanti (Al-DYAS, 2023)
Indonesia is one of the countries in the form of an organization, so its scope is very broad. This country was formed aims to improving the welfare oas mentioned in the opening UUD 1945 Constitution. According to Law Number 72 of 2005 chapter I paragraph II it states: "Village Fund Allocations are funds allocated by the district/city government for Villages, the sources of funds come from central and regional received by ditrict/city. The purpose of this study is to find how to evaluate the implementation of Village Fund Allocations in the Economic Sector of Bugis Village, Sape District, West Nusa Tenggara in 2022 and to find what factors influence the implementation of Village Fund Allocations in the Economic Sector of Bugis Village, Sape District, West Nusa Tenggara 2022. The type of research used is qualitative research. Informants in the study amounted 6 people. Data collection techniques namely Observation, Interview and Documentation. The results of this study is the Evaluation of the implementation of the Village Fund Allocation (ADD) in Bugis Village is not in accordance with the applicable regulations because the funds are earmarked for government administration rather than community empowerment.